(Ge, Mn): A ferromagnetic semiconductor for spin injection in silicon. (22nd February 2010) - Jamet, M.; Devillers, T.; Yu, I-S.; Barski, A.; Bayle-Guillemaud, P.; Rothman, J.; Favre-Nicolin, V.; Tardif, S.; Cherifi, S.; Cibert, J.; Grenet, L.; Noe, P.; et al.
Spin injection in semiconductors has been a long-standing issue in the field of spintronics for nearly 10 years. Only at the end of the 1990s, electrical spin injection in III-V semiconductors could be demonstrated using spin-light emitting diodes as spin detectors. Although silicon is the key material of microelectronics, spin injection in silicon could be achieved only recently in 2007. For this purpose, we have developed a new ferromagnetic semiconductor (Ge, Mn) that may be suitable for spin injection in silicon. Indeed this material is compatible with mainstream silicon technology and is predicted as a half-metallic ferromagnet. We have used low temperature molecular beam epitaxy to grow germanium films doped with manganese. Growth temperatures as well as Mn concentrations were kept low in order to avoid phase separation due to the low solubility of Mn in Ge. Careful structural and chemical analyses showed that (Ge, Mn) films are not diluted magnetic semiconductors. We rather observe high-TC ferromagnetic self-assembled nanocolumns in the germanium film with magnetic properties strongly dependent on growth parameters. We could clearly identify four different magnetic phases in Ge1−xMnx films: diluted paramagnetic Mn atoms in the germanium matrix, low TC (<200 K) nanocolumns, high TC nanocolumns (>400 K) and Ge3Mn5 clusters. The relative weight of each phase mainly depends on the growth temperature and to a lesser extent to Mn concentration. In parallel, we have developed methods to detect spin injection in silicon. Using a ferromagnetic metal with perpendicular magnetisation we could perform spin injection in silicon in the tunnelling regime through an alumina barrier. Spin detection was optically achieved using a SiGe/Si spin-light emitting diode without applying a magnetic field.